Recent developments in metal-catalyzed living radical polymerization - Kamigaito, Masami (Polymer journal, 2011)
This review presents a short overview of recent developments in metal-catalyzed living radical polymerization, mainly focusing on our recent research studies related to the subject. Metal-catalyzed living radical polymerization or atom transfer radical polymerization, which was originally developed via evolution of the metal-catalyzed Kharasch or atom transfer radical addition to chain-growth polymerization via reversible activation, has now been widely developed in many aspects. The effective metal catalysts include various transition metals, such as ruthenium, copper, iron and nickel, and highly active and versatile catalytic systems have been developed by designing ligands, applying lower oxidation metal species and using additives to widen the scope of controllable monomers and to minimize the amount of metal catalysts and the residual metals in the products. The development of the initiating systems has enabled the synthesis of a wide variety of novel, well-defined polymers, including end-functionalized, block, graft and star polymers, but also more complicated polymers possessing multiple controlled structures. Furthermore, metal-catalyzed living radical polymerization has been judiciously combined with stereospecific radical polymerization based on the use of polar solvents or Lewis acid additives, resulting in the dual control of the molecular weight and the tacticity of the resulting polymers and enabling the preparation of stereoblock and stereogradient polymers. The metal-catalyzed living radical polymerization has now been developed diversely in terms of the catalytic systems, controllable monomers, well-defined polymer structures and combinations with stereospecific radical polymerization. This review describes a short overview of recent developments in metal-catalyzed living radical polymerization mainly focusing on our recent research studies related to the subject.